A randomised placebo‐controlled trial examining the effect on hand supination after the addition of a suprascapular nerve block to infraclavicular brachial plexus blockade. (11th July 2016) - Flohr‐Madsen, S.; Ytrebø, L. M.; Valen, K.; Wilsgaard, T.; Klaastad, Ø.
Summary: Some surgeons believe that infraclavicular brachial plexus blocks tends to result in supination of the hand/forearm, which may make surgical access to the dorsum of the hand more difficult. We hypothesised that this supination may be reduced by the addition of a suprascapular nerve block. In a double‐blind, randomised, placebo‐controlled study, our primary outcome measure was the amount of supination (as assessed by wrist angulation) 30 min after infraclavicular brachial plexus block, with (suprascapular group) or without (control group) a supplementary suprascapular block. All blocks were ultrasound‐guided. The secondary outcome measure was an assessment by the surgeon of the intra‐operative position of the hand. Considering only patients with successful nerve blocks, mean (SD) wrist angulation was lower (33 (27) vs. 61 (44) degrees; p = 0.018) and assessment of the hand position was better (11/11 vs. 6/11 rated as 'good'; p = 0.04) in the suprascapular group. The addition of a suprascapular nerve block to an infraclavicular brachial plexus block can provide a better hand/forearm position for dorsal hand surgery.